A Capsule‐Type Microrobot with Pick‐and‐Drop Motion for Targeted Drug and Cell Delivery. Issue 9 (20th February 2018) - Lee, Seungmin; Kim, Soyeun; Kim, Sangwon; Kim, Jin‐Young; Moon, Cheil; Nelson, Bradley J.; Choi, Hongsoo
Abstract: A capsule‐type microrobot exhibits "pick‐and‐drop" (P&D) motion to hold a particle within a confined volume and transports it via a corkscrewing motion. The P&D motion is possible because the capsule‐type microrobot has two parts: a plunger and a cap. The fabricated microrobots are wirelessly controlled by a magnetic manipulator. Drugs or cells can be encapsulated in the container of the capsule‐type microrobot by the P&D motion or attached to the surface of the cap, which can be used as a supporting structure. Therefore, the capsule‐type microrobot can deliver suspended or adherent cells. The drug or cells are minimally exposed or not completely exposed to the surrounding fluid and do not experience shear force when encapsulated in the container. As a proof‐of‐concept, secure transportation of microparticles in the confined volume of the capsule via P&D motion is demonstrated. In addition, the cap is used as a scaffold for neuronal cell culture on a rat brain slice to demonstrate its biocompatibility and feasibility for targeted cell delivery. The proposed capsule‐type microrobot is suitable for diverse applications, as it protects the encapsulated materials. Abstract : A capsule‐type microrobot exhibits "pick‐and‐drop" (P&D) motion to hold a particle within a confined volume and transport it via a corkscrewing motion. Drugs or cells can be encapsulated in the container of the microrobot by the P&D motion or attached to the surface of the cap, which can be used as a supporting structure.